The Development of Geographical Information System and Other Databases Accessable through Mobile Equipments as well - Busznyák, János (Acta Agraria Kaposváriensis, 2004)
The rapid development of Information Technology is a constant challenge to data supply. The development and spread of mobile equipment capable of data collection (portable coputers, mobile phones, GPS equipments etc.) need a service system which can satisfy the users hungry for data. Data in different formats are to be organised into a database, and a standard method of access is to be ensured for user groups with different demand. Users should be able to access information with the help of any kind of equipment (mobile phone, palmtop, portable computer or desktop). There have been 2 different approaches to the problem. In our research program, the possibilities of information supply with the help of media server, and that of a mapserver have been examined. In both areas, the development of IT equipments (hardware, software) is so rapid nowadays that it forces traditional IT and other structures to change. This enforces changes in viewpoints in every field where wide band multiedia equipment telephoning, GPS positioning or any other up to date technology is used. In this presentation we will introduce the Geographical Information Technology and multimedia server developed by the University of Veszprém, Georgikon Faculty of Agriculture. We will present the research results obtained in the topic. Great attention is paid to the application of research results in our university instruction as soon as possible, which is supported by our already existing e-learning materials.